Pengaruh Disiplin Kerja, Kompetensi dan Komunikasi terhadap Kinerja Pegawai pada Dinas Kelautan dan Perikanan Aceh - Muhammad Rian Rizqi; Febyolla Presilawati; Amelia Rahmi (Jurnal Sains dan Ilmu Terapan, 2024)
This study aims to analyze the effect of work discipline, competence, and communication on employee performance at the Aceh Marine and Fisheries Service. The approach used in this research is quantitative. The study population consisted of all employees at the Aceh Marine and Fisheries Service, with the determination of the sample using the slovin formula. Data were collected through a questionnaire using a Likert scale as a measuring tool for the number of respondents of 78 employees, then analyzed using multiple linear regression methods. The results of the study using SPSS Statistics 26 show that partially, work discipline has a significant effect on employee performance, competence has no significant effect on employee performance and communication has a significant effect on employee performance. Simultaneously, work discipline, competence, and communication together have a significant influence on employee performance.